Exergaming no contexto da Oncologia Pediátrica - Nuno Filipe Bastos Rodrigues Patraquim (2014)
Every day, about 36 children are diagnosed with cancer. Regardless of ages, ethnic groups and socio-economic factors, cancer remains the number one cause of death by disease in children. In Portugal, there are about 350 new cases per year. Despite the medical and pharmaceutical advances in the paediatric oncology field, childhood cancer has been recording an annual increase of 1% in Portugal.This dissertation aims to contribute to improving the welfare of these children during their period of living with the disease. To verify what these children needed, an extensive literature review was performed, and institutes and associations - namely the IPO Porto and associations of parents of children with cancer - were contacted. This research clarified that these children do not have many play materials that explain them what is cancer in accordance to their age and development stage. Furthermore, these children develop a sedentary life, have physical problems and are lonelier. Besides this, these children frequently have difficulty adhering to various oncologic treatments.To overcome these problems, the video game Hope has been created. This video game is suitable for mobile devices, namely tablets. The video game's main character is a child who is acquiring super powers and capabilities to fight the bad cells and beat the disease. Through several interactive levels and a clean design, it is intended to teach children about cancer and motivate them to do physical exercises. Despite having greater impact in children with oncological disease, this video game can be played by all children.This video game has two fundamental components. By one hand, the serious game component allowed to build a video game that goes beyond entertainment and has the goal to teach cancer subjects. On the other hand, the exergaming component seeks to encourage the practice of physical exercise, using the front camera of mobile devices.Finally to validate this project we conducted two studies: the characterization of the population, and the prototype validation. The characterization of the population aimed to understand the tastes and routines of children in relation to video games, while the prototype validation aimed to evaluate the technology used for the exergaming component and to analyze the intrinsic motivation of the 13 children that tested the video game. The results showed that Hope is a proper tool to teach topics about cancer and to promote physical exercise.